EMPATI PADA PELAKU BULLYING DI SEKOLAH DASAR - Rizka Fibria Nugrahani (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2020)
The bully has a lack of empathy or in other words the bully cannot react to other people's feelings with the same emotional response that other people feel. Researchers want to see the empathy abilities by the bully in elementary schools. The research method used is a quantitative method with descriptive analysis. In measuring empathy using an empathy scale based on the empathy proposed by Davis (1983). Researchers provide an empathy scale to reveal responses to aspects of perspective taking, fantasy, empathic concern, and personal distress. Based on the results of research conducted, 60% of bullying actors have a moderate level of empathy. In this case, it is necessary to improve the bullying's empathy so that bullying behavior can be minimized or avoided.